Use of the Baidu Index to Analyze Spatiotemporal Characteristics of Online Attention to Adult Education - Yao Jiang; Qian Fu (Journal of Education, Health and Sport)
Purpose: This study aims to analyze the spatiotemporal evolution of public attention to "adult education" over the past decade. Methods: Using Baidu Index data from January 1, 2014, to November 1, 2024, we examined search trends, demand distribution, and user characteristics through trend research, demand mapping, and user profiling. Results: The online search index for adult education shows a fluctuating upward trend, with peaks in April and October each year. Demand mapping indicates interest in areas such as adult college entrance exams, self-study exams, educational institutions, exam schedules, registration, major selection, tuition, and application procedures. User profiling reveals higher attention from males aged 30~39 in Guangdong Province. Conclusion: Changes in online attention to adult education correlate closely with career aspirations, policy announcements, and social contexts.